A new species of Hoeneidia (Lepidoptera: Noctuidae, Noctuinae: Noctuini) from China - Babics, János; Benedek, Balázs; Saldaitis, Aidas (Zootaxa, 2014)
The monotypic genus Hoeneidia Boursin, 1954 was erected by Ch. Boursin for the H. cidarioides. In his article, Boursin (1954) included the genus Hoeneidia (Höneidia in the original description) with the trifine noctuids of the subfamily Noctuinae and between the genera Rhyacia Hübner, [1821] and Standfussiana Boursin, 1946. In his original description, Boursin (1954) indicated that the new genus was only provisional but several basic Hoeneidia characters did differentiate it from the other two genera.